2022
DOI: 10.2118/206007-pa
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ultrahigh-Temperature-Resistant Preformed Particle Gels for Conformance Control in North Sea Reservoirs

Abstract: Summary Preformed particle gels (PPGs) are 3D, crosslinked, dried polymer particles that can swell to several hundred times on contact with formation water. PPGs have been used extensively to control water production problems in reservoirs with conformance problems. The current state-of-the-art PPGs are polyacrylamide-based hydrogel compositions which lack long-term thermal stability under high-temperature and -salinity conditions. There are many oil reservoirs across the globe exhibiting condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Acidic and high-temperature, high-salinity environments can accelerate particle degradation and dehydration [31]. The degradation products may contain ketone, aldehyde, carboxylic ester groups, and monomer units, which can adsorb onto mineral surfaces, causing harm to the reservoir [32] and they are poorly adapted to low-permeability reservoirs [16]. Although polymers with temperature, salt, and acid resistance have been developed, their high costs make them economically unfeasible for widespread use.…”
Section: Gel Plugging Technologymentioning
confidence: 99%
“…Acidic and high-temperature, high-salinity environments can accelerate particle degradation and dehydration [31]. The degradation products may contain ketone, aldehyde, carboxylic ester groups, and monomer units, which can adsorb onto mineral surfaces, causing harm to the reservoir [32] and they are poorly adapted to low-permeability reservoirs [16]. Although polymers with temperature, salt, and acid resistance have been developed, their high costs make them economically unfeasible for widespread use.…”
Section: Gel Plugging Technologymentioning
confidence: 99%
“…After 18 months of aging at 150 • C, as shown in Figure 4, no degradation or dehydration was observeda nd the color change was due to residual oxygen. NMR spectra and SEM images indicated that the original chemical composition and crosslinking network structure were maintained even after aging; Schuman et al [51] investigated the performance of HT-PPGs under North Sea reservoir conditions, where the formation water salinity was approximately 7.6 × 10 4 mg/L, and the reservoir temperature ranged from 130 to 150 • C. The swelling ratio of HT-PPGs could reach over 30, and its stability lasted for more than 18 months, demonstrating excellent thermal stability and chemical stability. In simulation core experiments, HT-PPGs were able to reduce the permeability of 2 mm fractures to a millidarcy level.…”
Section: Re-crosslinkable Ppgmentioning
confidence: 99%
“…1−3 However, the original natural energy supply of these high-temperature reservoirs is usually very limited, and the reservoir permeability exhibits strong heterogeneity characteristics, leading to frequent occurrences of small volumes affected by water shut-off and even rapid excessive water production in oil production wells. 4,5 Therefore, it is urgently needed to study chemical flooding systems for hightemperature reservoirs to plug high-permeability water pathways and thereby improve oil recovery. 6,7 Commonly used chemical plugging systems mainly include in situ cross-linked polymer gels, particle gels, and foam gels.…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing demand for oil and gas resources and the continuous decrease recoverable conventional oil and gas reserves, more and more oil companies are turning their development goals to deeper, high-temperature petroleum reservoirs. However, the original natural energy supply of these high-temperature reservoirs is usually very limited, and the reservoir permeability exhibits strong heterogeneity characteristics, leading to frequent occurrences of small volumes affected by water shut-off and even rapid excessive water production in oil production wells. , Therefore, it is urgently needed to study chemical flooding systems for high-temperature reservoirs to plug high-permeability water pathways and thereby improve oil recovery. , …”
Section: Introductionmentioning
confidence: 99%